Is The Implementation of Citizen-Centric Service in E-Government the Key to a Sustainable Solution? - Fahmi, Rizal; Adara Huwaida, Ayesha; Purboningsih, Dewi; Azwari, Trisylvana; Dewi, Avela; Ariyani, Erma (Indonesian Association for Public Administration (IAPA), 2024)
The public demand for effective and efficient public services continues to grow over time, especially in the 21st century. Through the digitization of public services, also known as e-government, it is believed that these demands can be addressed, although criticisms remain regarding its implementation. The concept of citizen-centric service, which focuses on citizen-centered governance, could be a response to these criticisms. This research analyzes the implementation of e-government through a citizen-centric service approach. Using a literature review and content analysis methods, the author will examine various sources such as books, journals, articles, and so forth, supplemented by several relevant case studies aligned with the research topic. The research findings highlight the importance of the citizen-centric service approach, and this approach can serve as an optimal solution in creating inclusive and representative public policies. The conclusion of this study emphasizes that implementing e-government through a citizen-centric service approach not only has a positive impact but also broadens public participation. Furthermore, it is crucial to continuously improve digital infrastructure and digital literacy to support the more effective implementation of e-government.